(3JhGQjN GdGfHjGAs - (3eMeO Hf GdMSjf Hf ehSi GdQVj GdYdhj GdMSjfj GdehShj, CHh GdMSf GdTQja GdQVj,J (B406 (3g` s
(3ChdgG (B:s
(3adeG GNHQ QShd Gddg Udi Gddg Ydjg hSde Yf JaVjd Gddg hGUWaGAI EjGg s
(3BNQgG (B:s
(3eJHQckG ai Pdc GdMGd hGdeBd addg GdMeO Ydi GdGNJJGe s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B99 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B261s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3eJaQbGJs